The Role and Determinants for Developing Organizational Citizenship Behaviour in Organizations Based on the Example of Polish Non-Governmental Organisations - Schmidt , Joanna (Studia Oeconomica Posnaniensia, 2014)
The aim of this article is to identify the role and significance of Organizational Citizenship Behaviour (OCB) in promoting the development and supporting the effectiveness of an organization, with particular emphasis on non-governmental organizations as the subject of the research. The paper also aims to indicate the human-resource and organizational features which are conducive to the development of OCB in NGOs. The article presents the findings of research conducted among NGO teams throughout Poland (189 people in 29 organizations). The key findings indicate that the level of OCB is related to organizational rather than individual variables, which indicates the critical importance of the work environment in the development of OCB. Such elements as a high level of involvement, loyalty and a willingness to help others (as dimensions of OCB) seem to have a particular importance for the development of an organization.